Comparative characterization of mesenchymal stem cells from human dental pulp and adipose tissue for bone regeneration potential - Qiaoqiao Jin; Keyong Yuan; Wenzhen Lin; Chenguang Niu; Rui Ma; Zhengwei Huang (Artificial Cells, Nanomedicine, and Biotechnology)
Bone tissue engineering is an area of regenerative medicine that attempts to repair bone defects. Seed cells such as dental pulp stem cells (DPSCs) and adipose tissue-derived stem cells (ADSCs) are two of the most well-characterized cells for bone regeneration because their use involves few ethical constraints and they have the ability to differentiate into multiple cell types, secreting growth factors and depositing mineral. However, bone regeneration ability of these cells remains unclear. This study aimed to compare the bone formation capacity of DPSCs and ADSCs in vitro and in vivo. Studies revealed that DPSCs had enhanced colony-forming ability, higher proliferative ability, stronger migration ability and higher expression of angiogenesis-related genes. They also secreted more vascular endothelial growth factor compared to ADSCs. In contrast, ADSCs grew more slowly compared to DPSCs but exhibited greater osteogenic differentiation potential, higher expression of osteoblast marker genes, and greater mineral deposition. Furthermore, after DPSCs and ADSCs were implanted into a mandibular defect of a rat for 6 weeks, ADSCs showed visible bone tissue as early as week 1 and promoted faster and greater bone regeneration compared to the DPSC group. These results suggest that ADSCs might be more useful than DPSCs for bone regeneration.